SKILLS TO ENHANCE THE EFFECTIVENESS OF MATHEMATICS LESSONS IN PRIMARY EDUCATION - Diloram Fayazova (Western European Studies, 2024)
In this article, we talked about the effectiveness of the competency approach in the teaching of mathematics
Keywords: competence; mathematical literacy; media; reader